Executive functions and mathematical competence in Chinese preschool children: A meta-analysis and review - Zhong, Zhiyong; Xu, Yongqi; Jin, Ruining; Ye, Chen; Zhang, Mengmeng; Zhang, Hao (Frontiers in Psychology, 2022)
Although numerous studies have been conducted on the correlation between children’s executive functions and mathematical competence, the findings of those studies are inconsistent. This study used meta-analysis to investigate the correlation between executive functions and mathematical competence of preschool children in China, and then to explore the moderating effects of age, gender, and instruments. The researchers identified 22 studies on 3-7 years-old preschoolers in China from 2007-2021. The findings indicated that there was a moderately positive correlation between Chinese preschool children's executive functions and mathematical competence (r = 0 496), of which the effect size between mathematical competence and inhibition control is 0. 347, and the effect size for working memory is 0.432, with an effect size of 0.370 for cognitive flexibility. Furthermore, Moderation analysis suggests that the preschoolers' age, gender, and instruments affected the association between the executive functions and mathematical competence. The implications of these findings for theory and practice deserve further discussions.